Politik Hukum Insolvency Test Dalam Pembaharuan Hukum Kepailitan di Indonesia - Luqman Hakim; Nanda Diyan Saputra (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Legal politics as the basis for legal goals to be achieved in connection with the laws and regulations that have been enacted. Based on the provisions in the Bankruptcy Law, the requirements for a debtor to be declared bankrupt are very simple and easy even though they are actually in a solvent state. The legal consequence of the bankruptcy decision is that the debtor's assets will be placed in general confiscation by the Curator. This study uses a normative method. The result of this research is that the bankruptcy law in Indonesia has not accommodated the insolvency test mechanism as in developed countries. This causes a legal loophole if debtors who do not pay their debts, it is possible that creditors can intimidate the debtor by filing a bankruptcy application in the Commercial Court, even so, debtors who do not want to pay their debts to creditors can also apply for bankruptcy to the Commercial Court to avoid of the obligation to pay its debts.